PENGARUH GREEN ACCOUNTING DAN MATERIAL FLOW COST ACCOUNTING TERHADAP KEBERLANGSUNGAN PERUSAHAAN: PENGARUH GREEN ACCOUNTING DAN MATERIAL FLOW COST ACCOUNTING TERHADAP KEBERLANGSUNGAN PERUSAHAAN - Langgeng Prayitno Utomo (Jurnal Trial Balance, 2024)
This study is expected to be able to determine the effect of green accounting and material flow cost accounting on the sustainability of companies in mining companies. The data collection technique is carried out using the documentation data collection method. The data required in this study are secondary data from the financial reports of mining sector companies on the IDX for the 2019-2023 period. The sampling technique in this study uses purposive sampling. The analysis technique used is quantitative analysis. The results of this study indicate that: (1) Green Accounting has a significant effect on Company Sustainability; (2) Material Flow Cost Accounting has a significant effect on Company Sustainability.